Regional variation in COVID-19 vaccine uptake and intention in Nigeria: A computer assisted telephone survey. - Eniola Adetola Bamgboye; Rawlance Ndejjo; Nuole Chen; Rotimi Felix Afolabi; Steven N Kabwama; Mobolaji M Salawu; Segun Bello; Ayo Stephen Adebowale; Magbagbeola David Dairo; Lily L Tsai; Rhoda K Wanyenze; Olufunmilayo Ibitola Fawole (PLOS Global Public Health)
Globally, vaccination has been known to reduce the burden of infectious diseases such as COVID-19, with its effectiveness relying on public acceptance and widespread uptake. Despite the efforts put into the rapid development of SARS-COV-2 vaccines, uptake remains a major challenge in many countries especially those with large population dynamics like Nigeria. Most studies in Nigeria have assessed the uptake of the SARS-COV-2 vaccine among groups of people without consideration for ethno-cultural diversity. This study therefore explored COVID-19 vaccine uptake, its determinants and future intention among adult Nigerians in the six geopolitical zones of Nigeria. This was a cross-sectional survey using a Computer Assisted Telephone Interview. The study enrolled 1148 adults from one representative state across each of the six geopolitical zones that had a high COVID-19 burden. Trained research assistants interviewed consenting respondents using a pretested semi-structured questionnaire configured in Survey CTO between May and June 2022. Descriptive statistics were provided as means for continuous variables, while categorical variables were expressed as frequencies and percentages. Prevalence ratios were used as the measure of association. Respondents' age was 37.8±13.4 years, 53.9% were men and majority (65.2%) from southern Nigeria. About half (50.9%) of the respondents had not received vaccination, 29.7% were fully vaccinated, and 19.3% had incomplete dose. Majority (65.5%) of the respondents in the Northern states had not received SARS-COV-2 vaccine. Participants' age, sex, place of residence, occupation, religion, and region of residence were associated with vaccine uptake (p<0.05). About 70% of respondents who had not received the vaccine had the intention to receive the vaccine. A low rate of SARS-COV-2 vaccine uptake, particularly in the Northern region, and a high level of intention to receive the vaccine were reported among adult Nigerians. Focused efforts are needed in the Northern region to enhance SARS-COV-2 vaccine uptake.